Efecto de la ganadería extensiva sobre la regeneración arbórea de los bosques de la Sierra de Manantlán - Hernández Vargas, Guadalupe; Sánchez Velásquez, Lázaro R.; Carmona Valdovinos, Tomás F.; Pineda López, Ma. del Rosario; Cuevas Guzmán, Ramón (Instituto de Ecología, A.C., 2016)
The Las Joyas Field Station (LJFS) in the Sierra de Manantlán is characterized by a long history of anthropogenic disturbance. In 1988 a fence was established that delimited Las Joyas, excluding any anthropogenic disturbance. The fence divides different areas of cloud, pine and oak forests; consequently some forest areas have been under the pressure of cattle grazing and others not. The study was carried out in these forest with two replicates, where 180 plots of 2 x 2 m were randomly: 90 plots where established outside of the LJFS and the rest inside. In these plots, tree regeneration was recorded (specie, density and tree height), and 38 species from 33 families and 35 genus were recorded. The number of juvenile trees was significantly different in the cattle excluded sites and the cattle grazing sites (in all the cases, χ2 >7.5 y p <0.001). Floristic composition was also different. Inga hintonii and Alnus jorullensis are species that were not found in those sites with cattle grazing, suggesting that such species might be extinct with cattle grazing activities. Xylosma flexuosum and Pinus douglasiana showed significant importance values in the cattle excluded sites on cloud forest and pine-oak forest, respectively. In pine forest, Pinus douglasiana and Prunus serotina showed the highest importance values in both cattle excluded sites and cattle sites. It is concluded that cattle grazing is influencing a change on the species composition and is also declining the number of juvenile trees per hectare in the three types of vegetation studied.